Bulletin 97 Sampling and Analyzing Flue Gases - Henry Kreisinger; F. K. Ovrız (The National Institute for Occupational Safety and Health (NIOSH), 1915)
Some of the investigations conducted by the Bureau of Mines have for their object the collecting and disseminating of information regard- ing methods by which the fuels of the country may be most effi- ciently used. As the analysis of flue gases tends to develop better methods of firing, which in turn reduces waste of fuel, the Bureau of Mines in this bulletin presents for the benefit of those in charge of boiler plants and all other persons interested detailed information on methods of sampling and analyzing flue gases, and on the utilization of the analyses in promoting boiler-room economy. This bulletin is intended to be a companion to Technical Paper 80," and is written in plain and nontechnical language, as far as pos- sible, so that it may be readily understood by persons who have not had the advantage of a technical education. Whenever possible, illustrations of apparatus and methods of handling have been used rather than elaborate descriptions. The material presented in this report is arranged in two parts. The first part contains the description of the apparatus and the methods used in sampling and analyzing flue gases. The second part gives experimental results obtained with the different methods of sampling and collecting flue gas that are recommended in the first part of the report. Only simple apparatus and methods are considered, as they are accurate enough to show the large heat losses due to the use of too much air, and are also accurate enough to indicate any incomplete combustion losses of economic importance. Without doubt the loss due to large excess of air is the greatest one in the boiler room, and can usually be greatly reduced by making proper use of gas analysis. Before engineers in the isolated industrial plants can be induced to analyze for small traces of combustible gases, they must be first taught how to analyze for carbon dioxide (CO), and they must learn to appre- ciate the great possibilities of reducing loss from large excess of air. Furthermore, in the face of the great difficulty of obtaining a fair